The High Effect of Chemomobilization with High-Dose Etopside + Granulocyte-Colony Stimulating Factor in Autologous Hematopoietic Peripheral Blood Stem Cell Transplantation: A Single Center Experience - Güner, Şebnem Izmir (Hematol Rep, 2016)
Autologous hematopoietic stem cell transplantation (auto-HSCT) provides hematopoietic support after high-dose chemotherapy and is the standard of care for patients with multiple myeloma (MM), chemo sensitive relapsed high or intermediate grade non-Hodgkin’s lymphoma (NHL) and Hodgkin’s lymphoma (HL). However, yields of hematopoietic stem cells vary greatly between patients, and the optimal strategy to mobilize hematopoietic stem cells into peripheral blood for collection has not been defined yet. We investigated the efficacy and safety of chemo mobilization with an intermediate dose etoposide (VP-16; 200 mg/m(2) on days 1-3) and granulocyte-colony stimulating factor (G-CSF)(5 µg/kg twice daily from day 4 through the final day of collection). We reviewed our institutional experience with 91 patients (71 MM, 12 HL, 8 NHL) mobilized with this regimen. VP-16 + G-CSF resulted in successful mobilization in 95.55% of the patients (on one patient stem cell collection with plerixafor was applied), including 76 patients (83.52%) whose stem cells were collected successfully in a single day. Collection was managed between min. D8 and max. D17. Patient age, gender, exposure to previous irradiation and chemotherapy, previous mobilization attempts, and disease characteristics were not considered during selection. Adverse effects of the regimen included supportive transfusions and fevers requiring hospitalization or intravenous antibiotics. VP-16 and G-CSF appears to be a safe and effective mobilization regimen for patients with multiple myeloma, non-Hodgkin’s lymphoma and Hodgkin’s lymphoma undergoing autologous stem cell transplantation, producing excellent stem cell yield with the majority of patients requiring 1 day of apheresis.